Constraints in the adoption of Allanblackia stuhlmannii (Engl.) Engl. as agroforestry tree in East Usambara, Tanzania. Issue 3 (3rd July 2019) - Schmidt, Lars; Munjuga, Moses; Matunda, Bob I.; Ndangalasi, Henry J.; Theilade, Ida
ABSTRACT: Natural forests in the East Usambara Mountains provide villagers with several Non-Timber Forest Products. Useful trees are often retained when forests are converted to farmland. Allanblackia stuhlmannii is a common forest tree on farmland. Due to the high-quality seed oil, a wish to conserve the species and to provide farmers with income from seed sale, efforts have been made for large-scale production by smallholders. The strategy includes maintenance of existing trees on farmland and rejuvenation by planting. An adoptability survey was conducted among 225 seed collectors and farmers in 10 villages in East Usambara. Results showed that the traditional open fruit collection from farmland trees had become more restrictive. Adoption by farmers was slow. Although seeds were collected from standing trees, barriers to cultivation were long juvenile period, competition with crops, lack of space for tree planting and potential waste of land for male trees. The greatest obstacle was the preference for other tree species. Economic calculations showed that the production of Allanblackia seed was not competitive compared to clove and cinnamon. The study shows that although several NTFPs are collected, only Allanblackia was cultivated. The study questions whether Allanblackia cultivation, based entirely on smallholders, is sustainable.